Educational Expansion and Its Heterogeneous Returns for Wage Workers - Michael Gebel; Friedhelm Pfeiffer (Deutsches Institut für Wirtschaftsforschung (DIW), 2007)
This paper examines the evolution of returns to education in the West German labour market over the last two decades. During this period, graduates from the period of educational expansion entered the labour market and an upgrading of the skill structure took place. In order to tackle the issues of endogeneity of schooling and its heterogeneous returns we apply two estimation methods: Wooldridge's (2004) approach that relies on conditional mean independence and Garen's (1984) control function approach that requires an exclusion restriction. For the population of workers from the SOEP, we find that both approaches produce estimates of average returns to education that decrease until the late 1990s and increase afterwards. The gender gap in returns to education seems to vanish. Furthermore, we find that the so-called "baby boomer" cohort has the lowest average return to education in young ages. However, this effect disappears over time.
Keywords: J21; J24; J31; 330; Returns to Education; Human Capital; Skill Upgrading; Wage Work